Solitary Wave Solutions to the ZKBBM Equation and the KPBBM Equation Via the Modified Simple Equation Method (Journal of Partial Differential Equations, 2016)
In this article, the modified simple equation method (MSE) is used to acquire exact solutions to nonlinear evolution equations (NLEEs) namely the Zakharov- Kuznetsov Benjamin-Bona-Mahony equation and the Kadomtsov-Petviashvilli Benjamin- Bona-Mahony equation which have widespread usage in modern science. The MSE method is ascending and useful mathematical tool for constructing exact traveling wave solutions to NLEEs in the field of science and engineering. By means of this method we attained some significant solutions with free parameters and for special values of these parameters, we found some soliton solutions derived from the exact solutions. The solutions obtained in this article have been shown graphically and also discussed physically.